2022
DOI: 10.1007/s11239-021-02630-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of app-based remote warfarin management during COVID-19-related lockdown: a retrospective cohort study

Abstract: This study aimed to explore the effectiveness, and safety of internet-based warfarin management during the pandemic. In this single-center retrospective cohort study, we compared the safety and efficacy of online warfarin management using a smartphone app (the Alfalfa app) versus conventional outpatient clinic management from January 1, 2020 to March 31, 2020. Patients in the online management group used the Alfalfa app to communicate coagulation test results and other relevant information to a doctor or clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“… 23 Furthermore, the use of computer-assisted warfarin clinical algorithms dosing programs by the clinical pharmacist can improve warfarin dosing. 25 , 26 Combined genetic and clinical factors have proved to predict an algorithm for adjusting individual dosing of warfarin. 27 Some recent African studies have found other diverse variants relevant to predicting pharmacogenetics-based warfarin dosing additionally to those known in CYP2C9 and VKORC1 which indicate the necessity to conduct more pharmacogenomics studies on African population for other potential predictors for warfarin variability in response.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Furthermore, the use of computer-assisted warfarin clinical algorithms dosing programs by the clinical pharmacist can improve warfarin dosing. 25 , 26 Combined genetic and clinical factors have proved to predict an algorithm for adjusting individual dosing of warfarin. 27 Some recent African studies have found other diverse variants relevant to predicting pharmacogenetics-based warfarin dosing additionally to those known in CYP2C9 and VKORC1 which indicate the necessity to conduct more pharmacogenomics studies on African population for other potential predictors for warfarin variability in response.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine has shown positive impacts (easier access to information, alerting of caregivers, etc.) in the follow-up of patients treated with anti-vitamin K [ 17 ], or the monitoring of type I diabetes [ 18 ]. An application monitoring the recurrence of bronchial cancer has shown a better follow-up and an increase in life expectancy of patients [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognized as a pandemic by the World Health Organization ( World Health Organization, 2021 ). On 23 January 2020, China initiated the Level I response to public health incidents nationwide, which is the highest one ( Jiang et al, 2022 ), and slowed the spread of COVID-19 effectively. However, social distancing and stay-at-home orders, which were adopted to avoid the spread of COVID-19, posed unique challenges for patients on medications, requiring continued monitoring by clinic staff, such as warfarin treatment ( Kish and Lekic, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…“Internet + Anticoagulation clinic” (IAC) is a new approach for anticoagulation management, which is undoubtedly attractive to patients and clinical pharmacists, especially during the COVID-19 pandemic. To the best of our knowledge, only one previous study has investigated the effectiveness and safety of anticoagulation management provided by clinical pharmacists through the IAC during the COVID-19 pandemic ( Jiang et al, 2022 ), with small sample size and short-term follow-ups, providing preliminary conclusions that IAC improved anticoagulation quality. Therefore, more studies are encouraged to provide crucial evidence for application of IAC during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%